Моделирование измерительного индентирования нанопокрытий на титановой подложке - Смолин А. Ю. Алексей Юрьевич; Псахье С. Г. Сергей Григорьевич; Аникеева Г. М.; Сергеев В. В. Валерий Викторович (2013, 2013)
Заглавие с экрана